The religious dimension possibility in the degraded heroes of the tales of Marcal Aquino - Mendes, Fabio Marques [UNESP] (Pontificia Univ Catolica Sao Paulo-puc-sp, 2015)
This article proposes to contribute to the criticism and theological analysis regarding the understanding of the human being as God's image, from the New Brazilian Literary Realism. The demonic hero in his dramatic career, as conceptualized by Lukacs, will appear in the novels of Marcal Aquino, as in O Invasor (2002), Cabeca a Premio (2003) and Eu Receberia as Piores Noticias de Seus Lindos Labios (2005), but it was previously expressed in his collection of short stories entitled Familias Terrivelmente Felizes (2003), a work that focuses author's literary and stylistic project. Regarding to the Brazilian political and social history, these stories were written in a period of transition between the end of military rule and the nation opening and redemocratization, with twenty-one years separating the first story (1981) of the last (2002). We stress that no matter how the heroes socially marginalized in Familias Terrivelmente Felizes, constantly undergo death experiences that tear through their faces and subjugate them to the animalistic status, in situations marked by the absence of justice and welfare, the religious experience is still in force. The theological principle of imago Dei makes us realize that, made possible by the use of irony in the narrative.
Keywords: Marcal Aquino; New Realism; Brazilian Violence; Religious Experience